Application of computing science in trampoline movement research - Han, J.; Han, C. (2010 Third International Conference on Information and Computing, 2010)
A modeling and simulation method for trampoline movement based on sport biomechanics was developed. Taking tuck jump as example, the entire movement phase was divided into four parts: taking off from bending the knees, airborne, posturing and landing. Then the formulas were generated for modelling. Finally, simulation experiment was done with these formulas. The simulation results showed that this method is effective in trampoline movement research.